The mediating role of green investment in political connection and carbon information disclosure: Empirical evidence in emerging stock market - Astrid Maharani; Dian Agustia; Alfiyatul Qomariyah (Cogent Business & Management, 2023)
This study aims to expand this research by analyzing the mediating role of green investment in the influence of political connections on carbon information disclosure. The novelty of this study is the mediation model, which refers to a combination of upper echelons theory and stakeholder theory. The sample of this study totaled 197 firm years. This study uses a sample of energy and basic materials companies listed on the Indonesia Stock Exchange from 2017 to 2021. The results of the direct effect testing indicate that political connections affect carbon information disclosure. The findings show that green investment has a significant influence on mediating political connections and carbon information disclosure. This study confirms the mediating effect of the green investment variables. These results are supported by the robustness test results, which confirm the main conclusions. This indicates that the green investment made by the company mediates the political connection between the board of directors and the carbon information in its annual report or sustainability reporting. This study contributes to the literature on the role of green investment in mediating political connections in corporate top management to increase carbon information disclosure.
Keywords: 650; carbon information disclosure; green investment; political connection; stakeholder theory; upper echelons theory